On the determinants of currency crises: The role of model uncertainty - Jesus Crespo Cuaresma; Tomas Slacik (University of Innsbruck, Department of Public Finance, 2008)
We tackle explicitly the issue of model uncertainty in the framework of binary variable models of currency crises. Using Bayesian model averaging techniques, we assess the robustness of the explanatory variables proposed in the recent literature for both static and dynamic models. Our results indicate that the variables belonging to the set of macroeconomic fundamentals proposed by the literature are very fragile determinants of the occurrence of currency crises. The results improve if the crisis index identifies a crisis period (defined as the period up to a year before a crisis) instead of a crisis occurrence. In this setting, the extent of real exchange rate misalignment and financial market indicators appear as robust determinants of crisis periods.
Keywords: F31; F34; E43; 330; currency crisis; Bayesian model averaging; Währungskrise; Risiko; Institutionelle Infrastruktur; Bayes-Statistik; Schätzung; Welt